ESG performance and stability of New Quality Productivity Forces: From perspective of China's modernization construction - Xue, Runhua; Chen, Jiebin (International review of economics & finance, 2025)
This paper addresses the gap in existing literature regarding the factors that stabilize New Quality Productivity Forces (NQPF) within firms, particularly in the context of innovation-driven development and technological progress. While prior research has explored individual elements such as Environmental, Social, and Governance (ESG) performance, patent quality, and digital transformation, remains limited understanding of how these factors interact to influence SNQPF, particularly in the context of China's modernization drive. To fill this gap, we develop and empirically test a framework that examines the combined effects of ESG practices, patent quality, and digital transformation on SNQPF using a dataset spanning 2008 to 2022, comprising 3751 firm-year observations. The findings reveal that ESG performance significantly drives SNQPF improvement, aligning with China's focus on high-quality development that integrates economic growth with environmental and social responsibility. Additionally, we find that patent quality and digital transformation positively moderate the relationship between ESGP and SNQPF, highlighting the importance of technological innovation and intellectual property in fostering sustainable economic growth. This study provides new insights into optimizing ESG management strategies and contributes to the broader understanding of how innovation and sustainability practices interact to enhance SNQPF, supporting China's long-term modernization goals.